Integration of Archipelago Values into English Language Instruction in the English Language Education Program at Nusa Cendana University in the Era of Globalization - Marianus Tobias Pare; Maria Vincentia Chrisancta Fernandez; Theresia Putri Sevyani Welinza; Fransiska Krisnawati; Ida Nyoman Tri Darma Putra; Alfret Benu (Peneliti.net, 2026)
The use of English in learning in the era of globalization provides great benefits, but it can also create challenges to the national identity of the younger generation. This study aims to identify the challenges arising from this phenomenon and the importance of integrating Nusantara values in English learning. This research used a descriptive qualitative method with data collection techniques through two weeks of observation in the English Education Study Program, FKIP, Universitas Nusa Cendana, and interviews with one educator and three students. The results show that the dominant use of English can affect the decline of nationalism and students’ interest in local culture. Therefore, English learning needs to be accompanied by the cultivation and integration of Nusantara values so that students can remain globally competent without losing their national identity. Keywords: integration, globalization, values of nusantara, English learning, local culture.